Business combinations under common control (Part 1) - TAN, Pearl Hock-neo (Institutional Knowledge at Singapore Management University, 2021)
In a business combination under common control (BCUCC) the same party (or parties) ultimately controls the combining entities both before and after the business combination and this control is not transitory. BCUCC is not governed by any International Financial Reporting Standard (IFRS) issued by the International Accounting Standards Board (IASB). The IASB is undertaking a research project in response to stakeholder feedback of the diversity in accounting practice and released a Discussion Paper (DP) in November 2020 that sets out the Board’s preliminary views on reporting requirements. Our paper contributes to the discussion by proposing a contextual approach in determining the accounting method on BCUCC for the receiving entity (i.e. the entity which receives control of the transferred entity from another group entity). Two main methods are evaluated in this paper: the acquisition method which has a fair value focus and the predecessor method which has a historical cost focus. Typically, reporting entities have more incentives to use the predecessor method in the light of its beneficial reporting effects. The paper proposes that a BCUCC that contains commercial substance and results in a change in the timing, amounts and variability of cash flows to the receiving entity and its subsidiaries should be accounted as an acquisition under IFRS 3. The acquisition method better serves the information needs of the non-controlling interests and external stakeholders of the receiving entity when there is a real economic change of the receiving entity and its sub-group. The paper also argues that the lack of arms-length pricing does not pose insurmountable measurement issues and should not be the basis for the accounting choice.